2010
DOI: 10.1111/j.1475-6773.2010.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Medicaid Payment Acceptance at Outpatient Substance Abuse Treatment Programs

Abstract: Objective. To examine factors associated with Medicaid acceptance for substance abuse (SA) services by outpatient SA treatment programs. Data Sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…Accepting Medicaid may well be a part of an overall organizational commitment, regardless of type of ownership, to offering a wide range of evidence-based services that include ancillary and transitional services. Importantly, research indicates that only about half of states allowed Medicaid to pay for outpatient SAT services as part of Medicaid benefit offerings (Terry-McElrath et al, 2011). The data presented in this article suggest that state implementation of Medicaid policies allowing payment for SAT services may play a major role in improving the quality of treatment through facilitating core ancillary/transitional services and improving access for vulnerable populations.…”
Section: Discussionmentioning
confidence: 91%
“…Accepting Medicaid may well be a part of an overall organizational commitment, regardless of type of ownership, to offering a wide range of evidence-based services that include ancillary and transitional services. Importantly, research indicates that only about half of states allowed Medicaid to pay for outpatient SAT services as part of Medicaid benefit offerings (Terry-McElrath et al, 2011). The data presented in this article suggest that state implementation of Medicaid policies allowing payment for SAT services may play a major role in improving the quality of treatment through facilitating core ancillary/transitional services and improving access for vulnerable populations.…”
Section: Discussionmentioning
confidence: 91%
“…1 with a solid line: federal funding influence and state SA priority. State SA priority is defined as capacities to deliver services and legislative or bureaucratic support of SA treatment [29][30][31]. The framework also accounts for the three other institutional constraints in Hernandez & Uggen, represented by dashed lines.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A recent study examining the activation of state MH parity laws over 25 years found four significant predictors of activation: economic climate, political party control, presence of a strong advocacy group and interstate influences [28]. Other studies have examined the role of state-level institutional constraints for BH policy and are used to identify empirically testable institutional constraints: increasing treatment providers' use of psychotropic medications [29]; the acceptance of Medicaid funding at out-patient treatment centers [30]; and the differential provision of services between publicly and privately financed treatment providers [31]. We use constraints from these four papers to examine the activation decision empirically.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that Medicaid itself has historically been implemented differently across states in terms of which treatment services are covered (Garfield et al, 2010; Terry-McElrath et al, 2011). There has been a tendency within the SUD treatment field to regard Medicaid policies as a hindrance to innovation adoption, a perspective not supported by these data.…”
Section: Discussionmentioning
confidence: 99%
“…Collection of Medicaid policy data was beyond the scope of the current study, so we were unable to control for whether programs were located in states where Medicaid provided coverage for MAT and included these medications on its formulary. Resource dependence theory suggests that supportive state policies would likely result in greater implementation of MAT (Kubiak et al, 2009; Thomas et al, 2011), although the presence of a supportive state policy is no guarantee that programs will accept Medicaid payment (Terry-McElrath et al, 2011). …”
Section: Discussionmentioning
confidence: 99%